PENGARUH MODEL ACTIVE LEARNING QUIZ TEAM - Yuni Rhamayanti (Jurnal Cermatika, 2022)
The active learning quiz team model is one type of active learning that serves to liven up the atmosphere, increase their sense of responsibility for what they learn. The reason for using the active learning quiz team model is because this strategy is considered to make learning fun and students can actively participate in the learning process. At SMPN 2 Batangtoru Kab. South Tapanuli teachers have not used models, media or methods so that students' interest and activity have not been maximized. This study aims to explain: (1) how the effect of using the active learning quiz team model on the learning interest of class VIII students of SMPN 2 Batangtoru, Kab. South Tapanuli (2) how is the effect of using the quiz team model on the learning interest of class VIII students of SMPN 2 Batangtoru Kab. South Tapanuli and (3) how is the description of the activeness of class VIII students of SMPN 2 Batangtoru Kab. South Tapanuli. This type of research is quantitative research. The research design used is experimental research. In this study the population was all fourth grade students at SMPN 2 Batangtoru Kab. South Tapanuli with a total of 46 students with 23 students for the experimental class and 23 students as the control class.Sampling techniques and population samples. The data collection instruments used tests and questionnaires. The data analysis technique in this study used the T-test. Based on the calculated data, it showed that the average student interest in learning had a t-count value of 2.831 while t-table was 1.684, 0.05 and the average learning outcomes students have a t count value of 6.258 while t table 1.697, 0.05 the above variable shows t count > t table, meaning that Ho is rejected and Ha is accepted, so there is an effect of the quiz team strategy on interest in learning in mathematics learning for class VIII students